Antibiotics: Use and misuse in pediatric dentistry - F C Peedikayil (Wolters Kluwer Medknow Publications, 2011)
Antibiotics are commonly used in dentistry for prophylactic as well as for therapeutic purposes. Most often antibiotics are used in unwarranted situations, which may give rise to resistant bacterial strains. Dentists want to make their patients well and to prevent unpleasant complications. These desires, coupled with the belief that many oral problems are infectious, stimulate the prescribing of antibiotics. Good knowledge about the indications of antibiotics is the need of the hour in prescribing antibiotics for dental conditions.